International language proficiency standards in the local context: Interpreting the CEFR in standard setting for exam reform in Luxembourg. Issue 2 (3rd March 2020) - Brunfaut, Tineke; Harding, Luke
ABSTRACT: In the field of second and foreign language learning, the Common European Framework of Reference for languages (CEFR) is widely-used for setting language proficiency standards within European, and increasingly global, contexts. Few studies, however, have investigated the ways in which systemic, macro-level factors within national educational contexts may influence standard setting practices using the CEFR. In this paper, we explore this issue through an analysis of recorded discussions within standard setting sessions for the Épreuve Commune for English, a national English language examination in Luxembourg. The data reveals four key sources of influence on standard setting decision-making: Luxembourg's unique language ecology, streamed schooling, the national curriculum, and an ongoing exam reform project. Through this analysis, we argue that Luxembourg functions as a critical case illustrating the tension between international standards of language proficiency and local realities.